Development of Digital Atlas with Multiple Intelligences on the Materials of Cell Structure and Function to Improve Cognitive Thinking Ability of Senior High School Students - Ricky Janu Riyadi; Saptono, Sigit (Universitas Negeri Semarang, 2025)
Cell Structure and Function is one of the biology topics in senior high schools that needs to be concretized, as students cannot directly observe cellular structures and organelles without supporting tools. Learning this material requires observation of illustrations, logical reasoning, collaboration, and independent study. Relying solely on textbooks as the main learning source is considered less effective in mastering the concepts, which results in students’ incomplete cognitive understanding. Therefore, an additional teaching supplement that visualizes the material while accommodating students’ learning styles is necessary. This study aims to describe the characteristics of the developed atlas, analyze its validity, examine teachers’ and students’ responses, and evaluate the effectiveness of the atlas in improving students’ cognitive abilities. This research employed a Research and Development (R&D) design with eight stages: identifying potentials and problems, data collection, product design, expert validation, design revision, product trial, product revision, and usage trial. The subjects were XI MIPA A and XI MIPA E students at SMA N 1 Batang in the 2021/2022 academic year. Research instruments included interview sheets, validity sheets, teacher and student response questionnaires, and a 25-item multiple-choice test. Data were analyzed using descriptive quantitative percentages. The results showed that the developed atlas presented schematic illustrations and varied microscopic observations, linked cellular phenomena, encouraged logical reasoning through “let’s reason” prompts, facilitated discussions, and supported independent learning via YouTube videos. The validity test obtained a score of 96.6% (very good) from material experts and 87.5% (very good) from media experts. Teachers’ and students’ responses reached 90.7% and 91.2%, respectively, both categorized as very good. Effectiveness testing indicated improvements in cognitive thinking skills with the following N-Gain scores: remembering (C1) = 0.93 (high), understanding (C2) = 0.80 (high), applying (C3) = 0.76 (high), analyzing (C4) = 0.57 (moderate), and evaluating (C5) = 0.71 (high). Based on these results, the digital atlas incorporating multiple intelligences is proven effective in enhancing students’ cognitive thinking skills.